A paradigm shift in the EU's Common Foreign and Security Policy: From transformation to resilience - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2017)
The EU's Common Foreign and Security Policy (CFSP) is thriving. To the great surprise of many observers, there has been a strong increase in the conceptual and practical activity of the CFSP over the past few months, comparable only to its revival after the Kosovo crisis. In a speech in June 2017, German Chancellor Angela Merkel evoked the European spirit and affirmed that Europe would no longer be able to rely solely on others in the future. In all European policy areas that deal with foreign, security and defence issues, new institutions and political initiatives are being created, joint security research is being initiated, and new acts of law are being prepared. ow can we explain this renaissance of a policy area that was assumed dead? What legal and political dynamics have contributed to its revival? It is significant that foreign and security policy, which used to be purely political areas, are increasingly subject to legal reform and incorporation into the European legal community. Moreover, the ECJ is more and more active in dissolving the old distinctions between political and legal integration and between the EU's internal and external dimensions.
Keywords: 320